Online Education during COVID-19 in Punjab: A Study on Perception of Teachers - Kaur, Hardeep; Chadda, Ishu (Indian Journal of Educational Technology, 2022)
The closure of various educational institutions during the Covid-19 Pandemic resulted in an unplanned shift from the offline mode to the online mode of education. This shift created various perceptions amongst teachers as well as students. In this context, the present study aims to explore the perceptions of teachers regarding this transition. The teachers from various educational institutes of Punjab i.e. from schools, colleges and universities, were asked to give their opinion on the online teaching-learning practice. The structured questionnaire was framed and administered through Google form and drawn online on 250 teachers of Punjab during the period from 13-31 January 2021 (more than two weeks), using a snowball sampling technique. The present study deployed descriptive statistics and factor analysis. .The positive factors that impacted this transition were teacher’s characteristics, technical support from institutions, a supportive educational environment for students, social support, and a life-long learning process. The challenges faced by teachers are hedonic motivation, personal problems, and technical problems. The paper outlined that teachers preferred the regular and blended mode of education instead of the entire online system due to various constraints.